EFFECT OF THE CULTURAL SYSTEM ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN THE ENERGY SECTOR - Pinheiro, Alan Bandeira; Lima Sampaio, Thicia Stela; Barboza Guimarães, Daniel; Maria Dias Pedro Rebouças, Sílvia (Contabilidade Vista & Revista, 2021)
This study examines the effect of the cultural system on the disclosure of corporate social responsibility by companies in the energy sector. The survey analyzed a sample of 62 leading energy companies from 25 countries. The dependent variable is the level of environmental disclosure of the companies. The independent variables are composed by the cultural system of the analyzed countries, according to the Hofstede cultural dimensions. The data were analyzed using descriptive, inferential statistics, correlation, and regression of panel data. The findings show that in more individualistic and masculine cultures, companies disclose more CSR information. It was found that companies based in cultures with a higher level of indulgence and with a greater orientation for the long term tend to have greater environmental disclosure. The results show that the level of disclosure of corporate social responsibility is different depending on the country's cultural system. There are institutional pressures, which encourage companies to publish a more complete sustainability report. The results of this study have academic and managerial implications.